2022
DOI: 10.1108/hff-03-2022-0192
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of wavy porous layer, magnetic field and hybrid nanofluid with slot jet impingement on the cooling performance of conductive panel

Abstract: Purpose The purpose of this study is to analyze the impacts of combined utilization of multi-jet impinging cooling of nanofluids with magnetic field and porous layer on the cooling performance, as effective cooling with impinging jets are obtained for various energy systems, including photovoltaic panels, electronic cooling and many other convective heat transfer applications. Design/methodology/approach Finite element method is used to explore the magnetic field effects with the inclusion of porous layer on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 70 publications
0
8
0
Order By: Relevance
“…The results indicated that square jets provided the largest heat transfer when compared with circular jets 23 . Moreover, the various applications and uses of a magnetic field, a wavy porous layer, and a multijet and slot‐impinging system, along with more related studies regarding hybrid/nonhybrid nanofluids, are considered and can be observed here 24–36 …”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…The results indicated that square jets provided the largest heat transfer when compared with circular jets 23 . Moreover, the various applications and uses of a magnetic field, a wavy porous layer, and a multijet and slot‐impinging system, along with more related studies regarding hybrid/nonhybrid nanofluids, are considered and can be observed here 24–36 …”
Section: Introductionmentioning
confidence: 91%
“…23 Moreover, the various applications and uses of a magnetic field, a wavy porous layer, and a multijet and slot-impinging system, along with more related studies regarding hybrid/nonhybrid nanofluids, are considered and can be observed here. [24][25][26][27][28][29][30][31][32][33][34][35][36] The aforementioned evaluations indicate that several computational and experimental types of research studies on the forced laminar convection heat transfer of jet impingement on the flat target surface have been carried out. However, less attention is focused on the effect of metal foam across a jet impingement integrated with an ANSYS FLUENT-CFD and response surface methodology (RSM) approach optimization study under the pressure drop effect.…”
Section: Introductionmentioning
confidence: 99%
“…Mehta et al (2022b) computationally analyzed the hydrothermal performance for flow through a ribbed wavy channel by varying the number of ribbed and their shape: rectangular, semi-circular and triangular and observed that the rectangular ribbed-wavy channel has a higher performance factor among all the configurations in the regime: 50 # Re # 125. Additionally, numerous recent research investigations relating to heat transfer enhancement have been conducted using the irregular geometries, such as the 60°C hevron plate heat exchanger (Singh and Ghosh, 2022), wavy porous layer (Ouni et al, 2022), wavy surface with finite wall thickness (Borah et al, 2022), wavy channel with linearly varying amplitude (Kumar et al, 2022a(Kumar et al, , 2022b and novel wavy fin-and-circle tube heat exchanger having concave curved vortex generators (Song et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…They considered various flow regimes and different HT mechanisms. In Je-Im systems, nanofluid with porous systems have been considered in many studies (Zahmatkesh and Ali Naghedifar, 2017; Ouni et al , 2022; Siavashi et al , 2019; Selimefendigil and Öztop, 2020; Buonomo et al , 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The thickness of the PL was found to be an influencing parameter on the variation of average Nu while it was varied by about 17% when PL thickness was increased from 0.1 to 0.3. In Je-Im systems, nanofluid with porous systems have been considered in many studies (Zahmatkesh and Ali Naghedifar, 2017;Ouni et al, 2022;Siavashi et al, 2019;Selimefendigil and Öztop, 2020;Buonomo et al, 2019).…”
Section: Introductionmentioning
confidence: 99%